Quality Standards for Online Dakwah Content (Thematic Study in the Book Ṣaḥīḥ Muslim) - Putriany, Putriany; Zulfahmi Alwi; Arifuddin Ahmad; Ra’fah Jamilah Saadah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
The quality of online da‘wah content is a critical determinant of its effectiveness in conveying religious messages in the digital era. Its impact is highly contingent upon the faithful application of ethical principles rooted in the teachings of Islam. This study aims to identify quality standards for online da‘wah content based on the teachings of Ṣaḥīḥ Muslim. The research adopts a qualitative literature review (library research) approach, employing both normative–theological and sociological methods, and applies a thematic analysis of relevant hadith narratives. The findings indicate that quality standards for online da‘wah content, as reflected in Ṣaḥīḥ Muslim, comprise core values such as honesty, politeness, gentleness, friendliness, humility, moderation, exemplary behavior, refraining from slander and conflict, and fostering an optimistic outlook. The hadiths in Ṣaḥīḥ Muslim underscore the vital significance of preserving the authenticity of the da‘wah message and upholding ethical standards in its delivery — a matter of utmost relevance when addressing the challenges posed by digital platforms. To ensure that online da‘wah has a constructive and meaningful impact in nurturing the faith and moral character of its audience, it must be grounded in these high moral and intellectual standards.